Targeting GM-CSF in COVID-19 Pneumonia: Rationale and Strategies - Bonaventura, Aldo; Vecchié, Alessandra; Wang, Tisha S.; Lee, Elinor; Cremer, Paul C.; Carey, Brenna; Rajendram, Prabalini; Hudock, Kristin M.; Korbee, Leslie; Van Tassell, Benjamin W.; Dagna, Lorenzo; Abbate, Antonio (Frontiers in Immunology, 2020)
COVID-19 is a clinical syndrome ranging from mild symptoms to severe pneumonia that often leads to respiratory failure, need for mechanical ventilation, and death. Most of the lung damage is driven by a surge in inflammatory cytokines [interleukin-6, interferon-γ, and granulocyte-monocyte stimulating factor (GM-CSF)]. Blunting this hyperinflammation with immunomodulation may lead to clinical improvement. GM-CSF is produced by many cells, including macrophages and T-cells. GM-CSF-derived signals are involved in differentiation of macrophages, including alveolar macrophages (AMs). In animal models of respiratory infections, the intranasal administration of GM-CSF increased the proliferation of AMs and improved outcomes. Increased levels of GM-CSF have been recently described in patients with COVID-19 compared to healthy controls. While GM-CSF might be beneficial in some circumstances as an appropriate response, in this case the inflammatory response is maladaptive by virtue of being later and disproportionate. The inhibition of GM-CSF signaling may be beneficial in improving the hyperinflammation-related lung damage in the most severe cases of COVID-19. This blockade can be achieved through antagonism of the GM-CSF receptor or the direct binding of circulating GM-CSF. Initial findings from patients with COVID-19 treated with a single intravenous dose of mavrilimumab, a monoclonal antibody binding GM-CSF receptor α, showed oxygenation improvement and shorter hospitalization. Prospective, randomized, placebo-controlled trials are ongoing. Anti-GM-CSF monoclonal antibodies, TJ003234 and gimsilumab, will be tested in clinical trials in patients with COVID-19, while lenzilumab received FDA approval for compassionate use. These trials will help inform whether blunting the inflammatory signaling provided by the GM-CSF axis in COVID-19 is beneficial.